Literary Representations of Female Identity - Safoi Babana-Hampton (International Institute of Islamic Thought, 2002)
The essay examines the texts of the two women writers - Leila Abouzeid (from Morocco) and Nawal El Saadawi (from Egypt) - as offering two female perspectives within what is commonly referred to as "feminine" writing in the Arab Muslim world. My main interest is to explore the various discursive articulations of female identity that are challenged or foregrounded as a positive model. The essay points to the serious pitfalls of some feminist narratives in Arab-Muslim societies by dealing with a related problem: the author's setting up of convenient conceptual dichotomies, which account for the female experience, that reduce male-female relationships in the given social context to a fundamentally antagonistic one. Abouzeid's novel will be a case study of a more positive but also realistic and complex perspective on female experience ...